2013
DOI: 10.5152/jtgga.2013.68335
|View full text |Cite
|
Sign up to set email alerts
|

In vitro maturation may prevent the cancellation of in vitro fertilization cycles in poor responder patients: A case report

Abstract: In vitro maturation (IVM) is a promising technique that is used for the maturation of immature oocytes in laboratory conditions and preferred for use in patients with a diagnosis of polycystic ovary syndrome (PCOS) as an alternative to conventional in vitro fertilization (IVF) treatment. In this report, we present a case who surprisingly showed insufficient response to gonadotrophin stimulation during IVF treatment and whose cycle was retrieved from cancellation by using the in vitro maturation technique. As a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Jaroudi et al ( 22 ) were the first to report 3 cases in which IVM was used to secure cycles in poor responders, which resulted in deliveries of healthy babies. In a case report from Turkey, Yalcınkaya et al ( 23 ) studied IVM in a poor responder patient who achieved pregnancy and concluded that IVM could be used in poor responders as a good alternative. Braga et al ( 24 ) from Brazil used IVM to mature immature oocytes derived from stimulated cycles but they found that rescue spontaneous maturation of the oocytes did not contribute to clinical pregnancy rates in poor responder women.…”
Section: Discussionmentioning
confidence: 99%
“…Jaroudi et al ( 22 ) were the first to report 3 cases in which IVM was used to secure cycles in poor responders, which resulted in deliveries of healthy babies. In a case report from Turkey, Yalcınkaya et al ( 23 ) studied IVM in a poor responder patient who achieved pregnancy and concluded that IVM could be used in poor responders as a good alternative. Braga et al ( 24 ) from Brazil used IVM to mature immature oocytes derived from stimulated cycles but they found that rescue spontaneous maturation of the oocytes did not contribute to clinical pregnancy rates in poor responder women.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is a lack of perfect treatment for this group of patients, and most of their IVF cycles had to stop prematurely. In vitro maturation (IVM) is a fertility treatment option for poor responding PCOS patients to controlled ovarian stimulation (COS) [6,7]. However, the IVM procedure has various limitations and clinical concerns, including lower success rate of implantation, pregnancy, and live birth as well as a higher rate of aneuploidy and miscarriage [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Rescue in vitro maturation (IVM) is currently not a routine procedure in association with in vitro fertilization (IVF). Mehrdad Mir Farsi and colleagues' study has shown that 46% of the GV oocytes obtained from the stimulated cycles are matured, and about 25% of them are meiosis-associated anomalies (4).…”
mentioning
confidence: 99%